Sonographic Recognition of Agenesis of the Corpus Callosum - Atlas, Scott W.; Shkolnik, Arnold; Naidich, Thomas P. (American Journal of Neuroradiology, 1985)
Agenesis of the corpus callosum may be diagnosed successfully in vivo when sonograms demonstrate absence of corpus callosum; absence of pericallosal and cingulate sulci; “sunburst” pattern of sulci along the medial surface of the hemisphere; wide interhemispheric fissure; elevation of the third ventricle; small, laterally positioned frontal horns with concave medial borders; large, laterally positioned and inverted cingulate gyri; and Probst lateral callosal bundles. Comparison of necropsy specimens with sonograms from eight patients with callosal agenesis illustrates the anatomic basis for these diagnostic features.